PERSEPSI MASYARAKAT DESA SAYANG RW 03 KECAMATAN JATINANGOR KABUPATEN SUMEDANG TERHADAP PENTINGNYA PROTEKSI KENDARAAN BERMOTOR - Lienda Noviyanti (Dharmakarya : Jurnal Aplikasi Ipteks Untuk Masyarakat, 2019)
As the times and technology became more sophisticated, human needs and mobility also increased. One such technology is vehicle. It cannot be denied that motorized vehicles and cars have now become the most important parts of everyday life. Vehicle protection is very important to keep vehicles safe, especially in areas prone to theft. Protection of the vehicle itself is divided into two ways, namely by personal and insurance methods. The fact is that vehicle protection carried out by Desa Sayang residents is still very minimal, which is caused by a lack of knowledge and understanding of citizens about the importance of vehicle protection. Seen from only a few residents who have insurance services to protect their vehicles. Measuring the perceptions of residents of RW 03 Desa Sayang, Jatinangor Subdistrict, Sumedang Regency is divided into 2 things, namely knowledge (cognition) and behavior (konasi). Of the 97 informants interviewed, it was found that people's knowledge of insurance was not good. While their knowledge of vehicle protection in general is quite good. In addition, vehicle ownership also affects individual knowledge of insurance and vehicle protection. Unfortunately, protection of vehicles in the form of insurance is rarely done by residents because most are hampered in terms of costs and feel they do not need it. Therefore, a perception survey and vehicle protection socialization were made in Sayang Village, Jatinangor Sub-District, Sumedang Regency so that residents would be more aware of maintaining their vehicles.